Prospective association of social circumstance, socioeconomic, lifestyle and mental health factors with subsequent hospitalisation over 6–7 year follow up in people living with HIV. (January 2021) - Rein, Sophia M.; Smith, Colette J; Chaloner, Clinton; Stafford, Adam; Rodger, Alison J.; Johnson, Margaret A.; McDonnell, Jeffrey; Burns, Fiona; Madge, Sara; Miners, Alec; Sherr, Lorraine; Collins, Simon; et al.
Abstract: Background: Predictors of hospitalisation in people with HIV (PLHIV) in the contemporary treatment era are not well understood. Methods: This ASTRA sub-study used clinic data linkage and record review to determine occurrence of hospitalisations among 798 PLHIV from baseline questionnaire (February to December 2011) until 1 June 2018. Associations of baseline social circumstance, socioeconomic, lifestyle, mental health, demographic and clinical factors with repeated all-cause hospitalisation from longitudinal data were investigated using Prentice-Williams-Peterson models. Associations were also assessed in 461 individuals on antiretroviral therapy (ART) with viral load ≤50 copies/ml and CD4 count ≥500 cells/ µl. Findings: Rate of hospitalisation was 5.8/100 person-years (95% CI: 5.1–6.5). Adjusted for age, demographic group and time with diagnosed HIV, the following social circumstance, socioeconomic, lifestyle and mental health factors predicted hospitalisation: no stable partner (adjusted hazard ratio (aHR)=1.59; 95% CI=1.16–2.20 vs living with partner); having children (aHR=1.50; 1.08–2.10); non-employment (aHR=1.56; 1.07–2.27 for unemployment; aHR=2.39; 1.70–3.37 for sick/disabled vs employed); rented housing (aHR=1.72; 1.26–2.37 vs homeowner); not enough money for basic needs (aHR=1.82; 1.19–2.78 vs enough); current smoking (aHR=1.39; 1.02–1.91 vs never); recent injection-drug use (aHR=2.11; 1.30–3.43); anxiety symptoms (aHRs=1.39; 1.01–1.91, 2.06; 1.43–2.95 for mild and moderate vs none/minimal); depressive symptoms (aHRs=1.67; 1.17–2.38, 1.91; 1.30–2.78 for moderate and severe vs none/minimal); treated/untreated depression (aHRs=1.65; 1.03–2.64 for treated depression only, 1.87; 1.39–2.52 for depressive symptoms only; 1.53; 1.05–2.24; for treated depression and depressive symptoms, versus neither). Associations were broadly similar in those with controlled HIV and high CD4. Interpretation: Social circumstance, socioeconomic disadvantage, adverse lifestyle factors and poorer mental health are strong predictors of hospitalisation in PLHIV, highlighting the need for targeted interventions and care. Funding: British HIV Association (BHIVA) Research Award (2017); SMR funded by a PhD fellowship from the Royal Free Charity.